2020
DOI: 10.1007/s40211-020-00375-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual and group format adjunct therapy on social emotional skills for adolescent inpatients with severe and complex eating disorders (CREST-A)

Abstract: PurposeRelatively little is known about what psychological treatment adjuncts might be helpful for supporting people with the most severe and complex forms of anorexia nervosa (AN) with very low weight and malnutrition requiring inpatient admissions but targeting key perpetuating factors such as social emotional difficulties may be one way to advance knowledge. This pilot feasibility project reports on the development of an adolescent adaptation of Cognitive Remediation and Emotion Skills Training (CREST-A) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, we found that greater anhedonia was related to a number of variables indicating greater ED severity, including general measures of ED psychopathology (Boehm et al, 2018), longer duration of illness (Harrison et al, 2014), and excessive exercise (Davis & Woodside, 2002). Results from studies testing the effectiveness of CREST in AN suggested that social anhedonia may decrease after interventions that target cognitive flexibility and emotional skills (Harrison et al, 2020;Tchanturia et al, 2014Tchanturia et al, , 2015. Anhedonia was also related to constructs that did not measure ED symptoms, such as lower well-being (de Vos et al, 2021) and decreased positive emotion expression (Lang et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, we found that greater anhedonia was related to a number of variables indicating greater ED severity, including general measures of ED psychopathology (Boehm et al, 2018), longer duration of illness (Harrison et al, 2014), and excessive exercise (Davis & Woodside, 2002). Results from studies testing the effectiveness of CREST in AN suggested that social anhedonia may decrease after interventions that target cognitive flexibility and emotional skills (Harrison et al, 2020;Tchanturia et al, 2014Tchanturia et al, , 2015. Anhedonia was also related to constructs that did not measure ED symptoms, such as lower well-being (de Vos et al, 2021) and decreased positive emotion expression (Lang et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Social anhedonia was a primary outcome measure in four studies testing the effectiveness and feasibility of Cognitive Remediation and Emotional Skills Training (CREST; Adamson et al, 2018;Harrison et al, 2020;Tchanturia et al, 2014Tchanturia et al, , 2015 from the same research group. One study reported that individuals who completed individual or group formats of CREST did not experience a significant change in social anhedonia from pre-to posttreatment (Adamson et al, 2018).…”
Section: Longitudinal Changes In Anhedoniamentioning
confidence: 99%
See 1 more Smart Citation
“…However, current emotion‐focussed therapies generally include a focus on identifying the ways in which emotional experiences may influence engagement in disordered eating behaviours and learning adaptive self‐regulation skills that can be used in lieu of impulsive or compulsive behaviour. Some initial data support the effectiveness of emotion‐focussed therapies for both over‐ and under‐controlled EDs (e.g., Ben‐Porath et al., 2020; Harrison et al., 2020; Linardon et al., 2017; Reilly et al., 2020; Wonderlich et al., 2014). Of note, remission rates within this work are generally around 50%, highlighting a critical need to identify processes that may facilitate or interfere with treatment success.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, problems with mentalization and non-verbal social communication have been observed in patients with AN [50][51][52], and interventions that target social-emotional function are being explored in anorexia nervosa. Cognitive remediation and emotional skill training (CREST) augments treatment of severe AN, addressing social anhedonia, alexithymia, and quality of life [53,54]. Improvements in eating disorder symptoms, anxiety, and depression were observed with a brief group therapy intervention targeting self-attributions and perspective-taking for outpatients with eating disorders [55].…”
Section: Discussionmentioning
confidence: 99%